Characterization of slow charge transfer processes in differential pulse voltammetry at spherical electrodes and microelectrodes - Molina, A; Martinez-Ortiz, F; Laborda, E; Compton, R (2010)
The use of differential pulse voltammetry at spherical electrodes for the study of the kinetic of charge transfer processes is analyzed. An analytical solution is presented, valid for any value of the electrode radius, the heterogeneous rate constant and the transfer coefficient. Several reversibility criteria are established based on the variation of DPV peak with the duration of the potential pulses and the electrode radius. Moreover, general working curves for extraction of kinetic parameters from DPV experiments are given. The anomalous shape of DPV curves for quasireversible processes with small values of the transfer coefficient is reported. The effect of the presence of both electroactive species on DPV curves for quasireversible and irreversible systems is also studied. © 2010 Elsevier Ltd. All rights reserved.